2015
DOI: 10.1177/1087054715597410
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Presentation, Diagnosis, and Management of Children and Adolescents With ADHD Across European Countries

Abstract: European countries varied in diagnostic approaches and practice management of children/adolescents with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
10
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 35 publications
8
10
2
Order By: Relevance
“…Additional information on the reasons why children/adolescents did not receive BT is needed to differentiate between those who were not offered BT and those who were offered it but did not adhere to the program. The between-country variability (range 23%–77%) in the use of BT found in our survey is consistent with the substantial variability noted in a small-scale cross-national survey, which included psychiatrists/psychologists from several of the countries included in the CAPPA survey,40 and is also consistent with the between-country variability observed in a previous retrospective medical chart review study in six European countries (range 4.1%–50.7%) 25. In our survey, caregivers in Italy, Germany, and Spain reported the highest rates of BT use, possibly reflecting practice and cultural preferences, and good adherence to current ADHD treatment recommendations in these countries.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additional information on the reasons why children/adolescents did not receive BT is needed to differentiate between those who were not offered BT and those who were offered it but did not adhere to the program. The between-country variability (range 23%–77%) in the use of BT found in our survey is consistent with the substantial variability noted in a small-scale cross-national survey, which included psychiatrists/psychologists from several of the countries included in the CAPPA survey,40 and is also consistent with the between-country variability observed in a previous retrospective medical chart review study in six European countries (range 4.1%–50.7%) 25. In our survey, caregivers in Italy, Germany, and Spain reported the highest rates of BT use, possibly reflecting practice and cultural preferences, and good adherence to current ADHD treatment recommendations in these countries.…”
Section: Discussionsupporting
confidence: 90%
“…The CAPPA survey found a disconnect between such guidelines and caregiver-reported standard of care with respect to BT; a substantial proportion of children (44%) had not received BT, even though onlŷ25% of caregivers reported their child had severe/very severe ADHD at the time of the survey 26. Our finding of low BT use tallies with the findings from a previous retrospective medical chart review study in six European countries 25. The Multimodal Treatment Study of Children with ADHD showed that BT combined with medication did not have significantly greater benefits on core ADHD symptoms over medication alone 33.…”
Section: Discussionsupporting
confidence: 71%
“…Overall, 23-77% of children/adolescents were reported to have not received BT. This finding is consistent with a recent retrospective medical record review in which children/ adolescents with ADHD were followed for at least 2 years after diagnosis in six European countries (Setyawan et al, 2015). Only 15% of children/adolescents in the Italian sample received no BT, whereas BT was not used in at least half of cases (50-53%) in the Netherlands, France and the UK (Setyawan et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…ADHD diagnostic and management practices vary by geographic location (Hinshaw et al, 2011;Seixas et al, 2012;Setyawan et al, 2015). Medical and behavioural therapy (BT) help reduce ADHD symptoms (MTA Cooperative Group, 1999) but the availability of, and access to, different treatment modalities varies across countries (Hinshaw et al, 2011;Hodgkins et al, 2013;Seixas et al, 2012;Setyawan et al, 2015).…”
Section: Psychiatricmentioning
confidence: 99%
See 1 more Smart Citation